2022
DOI: 10.1002/bmc.5331
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of widely targeted metabolomics for the identification of chemical composition in epidermis, xylem and pith of Gleditsiae Spina

Abstract: Gleditsiae Spina, the thorn of Gleditsia sinensis Lam., has a long history of being used as a traditional medicine in East Asian countries. However, only a few biologically active substances have been identified from it. In this study, the epidermis, xylem and pith of Gleditsiae Spina, respectively Gs‐E, Gs‐X and Gs‐P, were studied. We used a widely targeted metabolomics method to investigate the chemical composition of Gs‐E, Gs‐X and Gs‐P. A total of 728 putative metabolites were identified from Gleditsiae Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Recent scientific literature has witnessed significant contributions regarding the metabolic composition, isolation, and identification from the thorns of G. sinensis ( Zhang et al, 2020 ; Zeng et al, 2023 ; Yu et al, 2017 ), the differences in chemical composition between the epidermis, xylem, and pith in thorns ( Ya et al, 2022 ), metabolite accumulation in different tissues of G. sinensis under conditions of drought stress and rehydration ( Liu et al, 2020 ). In our current study, a comprehensive analysis identified a total of 836 putative metabolites in the thorn ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent scientific literature has witnessed significant contributions regarding the metabolic composition, isolation, and identification from the thorns of G. sinensis ( Zhang et al, 2020 ; Zeng et al, 2023 ; Yu et al, 2017 ), the differences in chemical composition between the epidermis, xylem, and pith in thorns ( Ya et al, 2022 ), metabolite accumulation in different tissues of G. sinensis under conditions of drought stress and rehydration ( Liu et al, 2020 ). In our current study, a comprehensive analysis identified a total of 836 putative metabolites in the thorn ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids play essential roles as precursors of cuticular waxes in the plant cuticle and are specific to various membrane lipids, contributing to membrane homeostasis. It has been reported by Ya et al. (2022) that fatty acids accounted for a considerable proportion of the thorn metabolites and may contribute to its hardness ( Ya et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, only a few comprehensive profiles of GS chemical composition have been reported 25 . Besides, their identification mode mainly depended on the databases susceptible to imperfection accredited to nonuniform liquid‐phase MS conditions and incompetency for identifying novel compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] At present, only a few comprehensive profiles of GS chemical composition have been reported. 25 Besides, their identification mode mainly depended on the databases susceptible to imperfection accredited to nonuniform liquid-phase MS conditions and incompetency for identifying novel compounds. To solve these problems, we established a four-step data mining strategy combined with UHPLC-QTOF-MS/MS technology to profile the chemical composition of GS.…”
mentioning
confidence: 99%